Tall Fescue and E. coenophiala Genetics Influence Root-Associated Soil Fungi in a Temperate Grassland - Slaughter, Lindsey C.; Nelson, Jim A.; Carlisle, A. Elizabeth; Bourguignon, Marie; Dinkins, Randy D.; Phillips, Timothy D.; McCulley, Rebecca L. (Frontiers in Microbiology, 2019)
A constitutive, host-specific symbiosis exists between the aboveground fungal endophyte Epichloë coenophiala (Morgan-Jones & W. Gams) and the cool-season grass tall fescue (Lolium arundinaceum (Schreb.) Darbysh.), which is a common forage grass in the U.S., Australia, New Zealand, and temperate European grasslands. New cultivars of tall fescue are continually developed to improve pasture productivity and animal health by manipulating both grass and E. coenophiala genetics, yet how these selected grass-endophyte combinations impact other microbial symbionts such as mycorrhizal and dark septate fungi remains unclear. Without better characterizing how genetically distinct grass-endophyte combinations interact with belowground microorganisms, we cannot determine how adoption of new E. coenophiala-symbiotic cultivars in pasture systems will influence long-term soil characteristics and ecosystem function. Here, we examined how E. coenophiala presence and host × endophyte genetic combinations control root colonization by belowground symbiotic fungi and associated plant nutrient concentrations and soil properties in a two-year manipulative field experiment. We used four vegetative clone pairs of tall fescue that consisted of one endophyte-free (E−) and one E. coenophiala-symbiotic (E+) clone each, where E+ clones within each pair contained one of four endophyte genotypes: CTE14, CTE45, NTE16, or NTE19. After two years of growth in field plots, we measured root colonization of arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE), extraradical AMF hyphae in soil, total C, N, and P in root and shoot samples, as well as C and N in associated soils. Although we observed no effects of E. coenophiala presence or symbiotic genotype on total AMF or DSE colonization rates in roots, different grass-endophyte combinations altered AMF arbuscule presence and extraradical hyphal length in soil. The CTE45 genotype hosted the fewest AMF arbuscules regardless of endophyte presence, and E+ clones within NTE19 supported significantly greater soil extraradical hyphae compared to E− clones. Because AMF are often associated with improved soil physical characteristics and C sequestration, our results suggest that development and use of unique grass-endophyte combinations may cause divergent effects on long-term ecosystem properties.